Advanced studies in energy efficiency and built environment for developing countries : Proceedings of IEREK Conferences: improving sustainability concept in developing countries (ISCDC-2), Egypt 2017 and alternative and renewable energy quest in architecture and urbanism (AREQ-2), Spain 2017 (Advances in science, technology & innovation IEREK interdisciplinary series for sustainable development / editorial board members Anna Laura Pisello [y otros diecisiete], 2019)
This edited volume consists of three parts. It is a culmination of selected research papers presented at the second version of the international conference on Improving Sustainability Concept in Developing Countries (ISCDC) and the second version of the international conference on Alternative and Renewable Energy Quest in Architecture and Urbanism (AREQ), organized by IEREK in Egypt, 2017. It discusses major environmental issues and challenges which threaten our future. These include climate change impact, environmental deterioration, increasing demand for energy and new approaches for alternative renewable energy sources which became a necessity for survival. In addition to addressing the different environmental issues witnessed today, research presented in this book stressed on the need of sustainably shaping buildings and cities using renewable energy sources. Topics included in this book are (1) Resilience in the Built Environment, (2) Design for energy-efficient architecture and (3) Alternative and Renewable Energy Resources Quest in Architecture and Urbanism. The book is of interest to researchers and academicians who continuously aim to update their knowledge in these fields, as well as decision makers needing the enough knowledge to carry out the right decisions towards the benefit of the environment and society.